Znaczenie nieobecności ojca w narracjach Dorosłych Dzieci Rozwiedzionych Rodziców - Piotrowska, Maja (Karkonoska Państwowa Szkoła Wyższa, 2011)
For the years our thinking about parenthood was dominated for the scheme of relation mother – child. Contemporary the role the father plays in the family and during bring up the child is more preciours. The role of father in the family is of Vital importance, but many fathers cannot play it. Beside good ones, there are also the absent, weak and “poisonous” fathers. “Poisonous” fathers are the worst ones - destroying the childs' personality by using physical or psychological violence. A good father is a real gift in the childs' life. This article presents the narrations of theAdult Children of Parents' Divorce regarding their fathers from their childhood. The article shows huge fathers' influence on the life and social development their children. That is proved, that divorce breakes off the emontional and spiritual bonds between parents (expecialy fathers) and their children after divorce.
Keywords: rodzina; rozwód; ojciec; rodzice